2017
DOI: 10.1111/jen.12466
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of “Candidatus Liberibacter asiaticus” in a Florida population of Asian citrus psyllid

Abstract: The incidence of a bacterium "Candidatus Liberibacter asiaticus" was assessed in a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 32 publications
(59 reference statements)
3
31
1
1
Order By: Relevance
“…However, Ct values were significantly lower (indicating higher C Las titer) in infected females compared to infected males (P<0.001, Table 4 ), which supports field observations on the rate of infected D . citri in Florida [ 41 ]. Strikingly, D .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Ct values were significantly lower (indicating higher C Las titer) in infected females compared to infected males (P<0.001, Table 4 ), which supports field observations on the rate of infected D . citri in Florida [ 41 ]. Strikingly, D .…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously reported that substantial variability exists in the infection rate of in D . citri field populations [ 40 , 41 ], which can be attributed to genetics and/or environmental or host plant factors. In this work, we established D .…”
Section: Introductionmentioning
confidence: 99%
“…Also, there were no gender related differences in the proportion of insects that were CLas-infected, inoculative, or in their CLas titer. Similarly, no gender differences were reported from laboratory reared, CLas-infected D citri adults 15 , 22 , but the proportion of infected females was generally higher than that of males in field-collected samples from Florida 29 . Since D. citri females live much longer than males 30 this might affect their rate of infectivity under field conditions, which may bias the proportion of infected psyllids slightly toward females.…”
Section: Discussionmentioning
confidence: 88%
“…Several previous studies have been conducted to investigate the population dynamics of ‘ Ca. L. asiaticus’ and its relation to root growth and flushing cycles of citrus and non-citrus hosts [ 138 , 139 , 140 , 141 , 142 ] as well as within the population of its vector, D. citri [ 140 , 143 ]. In addition, numerous studies focused on the association between citrus flushing cycles and the population dynamics and demography of D. citri [ 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 ].…”
Section: Association Between Citrus Flushing Cycles and Populationmentioning
confidence: 99%